(untitled) (Journal of Philosophy Culture and Political Science, 2021)
The Article investigates the content and essence of religious culture. As elements of religious culture presents social relationships, systems of knowledge and practices based on religious outlook, embodied in religious organizations, material and spiritual results of religious activities. It is noted that the idea which exists in western science of the essence of religious phenomena reflects the model of Christian religiosity which is close to the other abrahamic religions, but the idea is not universal. Religiosity is considered in connection with religion as the way it manifests itself in social being and social consciousness. The essence of religious culture is revealed in the adoption and active embodiment of the relationship knowable world, the real world and the divine, the unknowable, but extremely desirable, in the pursuit of rapprochement person with his transcendental, geostationary ideal. Key words: religious culture, essentiality, acceptance, activity, geostationary ideal.